Excusing Corporate Wrongdoing and the State of Nature - Silver, Kenneth; Garofalo, Paul (Academy of Management Review, 2025)
Most business ethicists maintain that corporate actors are subject to a variety of moral obligations. However, there is a persistent and underappreciated concern that the competitive pressures of the market somehow provide corporate actors with a far-reaching excuse from meeting these obligations. Here, we assess this concern. Blending resources from the history of philosophy and strategic management, we demonstrate the assumptions required for and limits of this excuse. Applying the idea of “the state of nature” from Thomas Hobbes, we suggest that corporate actors would be excused from duties if complying with them threatened their vital interests. We show how this excuse is not available for most individuals within firms; instead, it is an excuse perhaps available to firms themselves, but only given substantive assumptions about corporate personhood. For those willing to make these assumptions, we apply the competitive advantage construct to delimit the scope of this excuse. We suggest that firms are excused from fulfilling an obligation when complying leads to a competitive disadvantage, as this imperils the firm’s vital interests. After revealing why this excuse does not generalize, we conclude by considering when we should reform the market to avoid the legitimacy of this excuse.